2019
DOI: 10.18632/oncotarget.27285
|View full text |Cite
|
Sign up to set email alerts
|

Mesangiogenic progenitor cells are forced toward the angiogenic fate, in multiple myeloma

Abstract: Multiple myeloma (MM) progresses mainly in the bone marrow where the involvement of a specific microenvironment plays a critical role in maintaining plasma cell growth, spread, and survival. In active disease, the switch from a pre-vascular/non-active phase to a vascular phase is coupled with the impairment of bone turnover. Previously, we have isolated Mesangiogenic Progenitor Cells (MPCs), a bone marrow population that showed mesengenic and angiogenic potential, both in vitro and in vivo. MPC differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Several studies have shown, in human liposarcoma and melanoma, the presence of alterations in specific tumor ECs: a heterogeneous population probably trans-differentiated from VSCs [ 105 ]. Our research group also identified specific MPCs in multiple myeloma (MM), demonstrating their involvement in both tumor growth and osteolysis [ 106 ]. These MPCs contributed to the formation of new blood vessels and reduced osteoblastogenesis.…”
Section: Vascular Progenitor Cells In Cancersmentioning
confidence: 99%
“…Several studies have shown, in human liposarcoma and melanoma, the presence of alterations in specific tumor ECs: a heterogeneous population probably trans-differentiated from VSCs [ 105 ]. Our research group also identified specific MPCs in multiple myeloma (MM), demonstrating their involvement in both tumor growth and osteolysis [ 106 ]. These MPCs contributed to the formation of new blood vessels and reduced osteoblastogenesis.…”
Section: Vascular Progenitor Cells In Cancersmentioning
confidence: 99%
“…They reportedly play an immunomodulatory role in tumor microenvironment, also contributing to local tumor aggressiveness in some hematological malignancies. [89][90][91] Due to their anti-inflammatory effects and their interaction with macrophages, many trials use MSC to treat aggressive GVHD, 92 but in some cases MSCs were also enginereed Open access to hyperexpress cytokines as IFN-γ and inoculated within tumor tissue. 93 The administration of systemic thirdparty MSC in patients with steroid refractory acute and chronic GVHD showed response rates up to 70%.…”
Section: Cellular Immunotherapy For Covid-19mentioning
confidence: 99%